Bad magic - Bosch, Pseudonymous; Ford, Gilbert (New York : Little, Brown and Co., 2014)
Thirteen-year-old Clay, a boy who no longer believes in magic, tags graffiti on his classroom wall and, as punishment, is sent to a camp for wayward kids located on a volcanic island, where eccentric campmates abound, a ghost walks among the abandoned ruins of a mansion, and a dangerous force threatens to erupt with bad magic.
Publisher's Weekly, July 2014.
Kirkus Review, August 2014.
5.2
3-6
730L
W
Keywords: Magic -- Juvenile fiction; Camps -- Juvenile fiction; Magic -- Fiction; Camps -- Fiction; Magic -- Fiction; Camps -- Fiction; Magic -- Fiction; Camps -- Fiction